Modelo de recompensa total y su efecto en el desempeño laboral de los colaboradores de la empresa Alviña Trujillo 2021 - Ortiz Julca, Deysi Carolina (2022)
The present research seeks to determine the relationship between the total reward and the work performance of the collaborators of the bakery industry Alviña EIRL, Trujillo 2021, a quantitative design was used, of the descriptive-correlational type, and the questionnaire was applied as an instrument, the population was formed by the collaborators of the preparation, sales and administrative areas. It was concluded that 60.7% of the employees mentioned that there is a model of total reward at an average level and excellent work performance, as shown in Table 3, while 17.9% indicated that there is a model of total reward at an average level and regular work performance. The contrasted results allow us to conclude that the total reward model shown by the Alviña EIRL bakery industry towards the workers is offered at medium levels, as for the work performance, most of them have an excellent performance, as for the results and multidimensional dimensions, they were observed at excellent levels, while the relevance for the organizational goal was observed at a regular level; However, it is recommended, through the assistant manager, that the total rewards model is written and improvements are implemented to strengthen the labor bond of employees and thus improve job performance in more than 90% of the company's employees.